In the Land of the Eastern Queendom The Politics of Gender and Ethnicity on the Sino-Tibetan Border - Jinba, Tenzin (University of Washington Press, 2013)
The story underlying this ethnography began with the recent discovery and commercialization of the remnant of an ancient queendom on the Sichuan-Tibet border. Recorded in classical Chinese texts, this legendary matriarchal domain has attracted not only tourists but the vigilance of the Chinese state. Tenzin Jinbas research examines the consequences of development of the queendom label for local ethnic, gender, and political identities and for state-society relations.